Incidence, associated factors, and effect on renal function of amoxicillin crystalluria in patients receiving high doses of intravenous amoxicillin (The CRISTAMOX Study): A cohort study. (March 2022) - Demotier, Sophie; Limelette, Anne; Charmillon, Alexandre; Baux, Elisabeth; Parent, Xavier; Mestrallet, Stéphanie; Pavel, Simona; Servettaz, Amélie; Dramé, Moustapha; Muggeo, Anaelle; Wynckel, Alain; Gozalo, Claire; et al.
Summary: Background: Amoxicillin crystalluria (AC), potentially responsible for acute kidney injury (AKI), is reported more and more frequently in patients treated with high doses of intravenous amoxicillin (HDIVA). The main objective of this study was to evaluate AC incidence in these patients. The secondary objectives were to identify factors associated with AC and to evaluate its impact on the risk of AKI. Methods: This multicentre, observational, cohort study was conducted between Mar 18, 2014 and Aug 16, 2019 in Dijon, Nancy, and Reims University Hospitals as well as Châlon-sur-Saône, Charleville-Mézières, and Troyes general hospitals in France. Adult patients (≥18 years) treated with HDIVA and having been tested for AC at least once during treatment were included. Clinical, biological, and therapeutic characteristics of the patients were collected. A univariable mixed logistic regression model assessed the factors associated with AC. A multivariable Cox model with AC as a time-dependent variable assessed the prognostic factors for AKI. ClinicalTrials.gov number: NCT02853292. Findings: Of the 112 included patients, 27 (24.1%, 95% CI [16.2-32.0]) developed at least one episode of AC within a mean of 5.1 days. The factors associated with its occurrence were the concomitant use of angiotensin converting enzyme (ACE) inhibitors (OR=4.6, 95% CI [2.2-9.3], p<0.0001) and the decrease of urinary pH (OR=2.1 for one pH point decrease, 95% CI [1.2-3.7], p=0.009). 20 patients (17.9%) presented with AKI, within a mean time of 10.9 days. The main factor associated with the occurrence of AKI was the occurrence of AC (aHR=7.4, 95% CI [2.5-22.2], p=0.0003). Interpretation: AC occurred in a quarter of patients treated with HDIVA and was highly prognostic of AKI. Funding: None.